Evaluation of Internal Auditory Canal Structures in Tinnitus of Unknown Origin - Polat, Cahit; Baykara, Murat; Ergen, Burhan (Korean Soc Otorhinolaryngol, 2014)
Objectives. The aim Of the present study was to evaluate the internal auditory canal (IAC) and the nerves inside it to define possible structural differences in cases with subjective tinnitus of unknown origin. Methods. Cases applying to the ear, nose and throat department with the complaint of tiimitus with unknown origin and having normal physical examination and test results were included in the study (n=78). Patients admitted to the radiology clinic for routine cranial magnetic resonance imaging (MRI) and whose MRI findings revealed no pathologies were enrolled as the control group (n=79). Data for the control group were obtained from the radiology department and informed consent was obtained from all the patients. Diameters of the IAC and the nerves inside it were measured through enhanced images obtained by routine temporal bone MRIs in all eases. Statistical evaluations were performed using Student t-test and statistical significance was defined as P<0.05. Results. Measurements of IAC diameters revealed statistically significant differences between the controls and the tinnitus group (P < 0.05). Regarding the diameters of the cochlear nerve, facial nerve, inferior vestibular nerve, superior vestibular nerve, and total vestibular nerve, no statistically significant difference was found between the controls and the tinnitus group. Conclusion. Narrowed IAC has to be assessed as an etiological factor in cases with subjective tinnitus of unknown origin.
Keywords: Tinnitus; Diameter of internal auditory canal; Cochlear nerve; Vestibular nerve; Facial nerve; Magnetic resonance imaging